Synthesis of Simplified Halogenated Chondramide Derivatives with Strong Cytostatic Properties (Eur. J. Org. Chem. 12/2015). Issue 12 (April 2015) - Becker, Dominic; Kazmaier, Uli
Abstract : The cover picture shows fruiting bodies of the terrestrial myxobacterium Chondromyces crocatus, the producers of a wide range of closely related compounds called chondramides. These cyclic depsipeptides are stabilizing the actin cytoskeleton, which induces apoptosis in cancer cell lines (right upper corner) in the low nM range. Introduction of an additional chlorine substituent onto the β‐tyrosin moiety allows the removal of all methyl groups (including stereogenic centers) without a significant drop in activity. The authors thank Dr. Ronald Garcia and Dr. Jennifer Herrmann from the Helmholtz Institute for Pharmaceutical Research Saarland (HIPS, Saarbrücken) for providing the picture of the Chondromyces strain, cytotoxicity studies and the picture of the cancer cells. Details are discussed in the article by D. Becker and U. Kazmaier on2591 ff .